Pancreatic Evaluation in Dogs Using Different Ultrasonographic Techniques-Preliminary Results - Avante, Lopes Michelle [UNESP]; Rossi, Feliciano Marcus Antônio [UNESP]; Rossi, Feliciano Marcus Antônio; Ramirez, Uscategui Ricardo Andres [UNESP]; Cristina, Maronezi Marjury [UNESP]; Aguila, Silva Priscila Del [UNESP]; Ricardo, Pozzobon; Rodrigues, Simões Ana Paula [UNESP]; Priscila, Silva [UNESP]; Beatriz, Gasser [UNESP]; Letícia, Pavan [UNESP]; Nogueira, Aires Luiz Paulo [UNESP]; et al. (De Gruyter, 2020)
The aim of this study is to describe the preliminary results on the accuracy of ultrasonographic techniques such as elastography, contrast enhanced ultrasound (CEUS) and Doppler in determining pancreatic changes. Twenty-five dogs, males and females, aged 1-14 years, were studied. Sixteen animals had no clinical signs of pancreatic disease (GS) and nine presented signs of pancreatic disorders (GD). All animals from GD presented sonographic changes in B-mode and qualitative elastography, with shear-wave velocity (SWV) higher (2.4±0.5m/s) in GD (p=0.014) than GS (1.9±0.3m/s) resulting in 78% sensitivity and 69% specificity in the identification of pancreatic changes. Regarding Doppler mode, no differences were observed between groups with color mapping or pulsed wave Doppler. The values obtained with CEUS did not differ between groups. Elastography is a promising technique for differential diagnosis of pancreatic changes because of its sensitivity and specificity, while the other techniques did not show diagnostic accuracy.
Keywords: elastography; hemodynamics; pancreatic diseases; Ultrasonography